Digital Workflow for Indirect Bonding with 2D Lingual Brackets: A Case Report and Procedure Description - Federico Rosti; Maria Francesca Sfondrini; Davide Bressani; Marina Consuelo Vitale; Paola Gandini; Andrea Scribante (Case Reports in Dentistry)
Objective. During orthodontic therapy, accuracy in bonding procedures makes it easier to correct tooth alignment by decreasing the need for midcourse corrections by changing bracket positions. Indirect bonding allows the transfer of the appliance components from model casts to patient’s teeth potentially meaning shorter appointments for bracket bonding and rebonding and best comfort during chairside practice. At the same time, there has been a steady increase in requests for invisible lingual orthodontic treatment. Clinical Considerations. Accordingly, the aim of the present report is to illustrate the workflow to realize a complete digital indirect bonding for lingual brackets (2D, Forestadent). The procedure starts with intraoral digital scans, digital 3D model, and virtual bracket positioning, ending with the realization of a CAD-CAM prototyped transfer tray. A 3D intraoral scanner (True Definition, 3M) is used to create digital scans and digital models. A virtual bracket positioning is performed using software (NemoCast, Dentaurum), and a prototyped transfer tray is created by a CAD-CAM device. 2D lingual brackets were positioned inside the tray, so the appliance was bonded to the dental surface using light curing adhesive resin. Conclusions. During orthodontic treatment, CAD/CAM technology could help clinicians. Computer-constructed transfer trays can reduce clinician error and improve the everyday workflow in the office.